Scalable spray deposition process for highly uniform and reproducible CNT-TFTs. (1st December 2016) - Loghin, F; Colasanti, S; Weise, A; Falco, A; Abdelhalim, A; Lugli, P; Abdellah, A
Abstract: Carbon nanotubes (CNTs) are one of the most interesting materials for printed electronics. The possibility to obtain CNT thin-films via solution-processing techniques has opened the way to low-cost applications such as, but not limited to, thin-film transistors (TFT). In this paper we present a spray deposition technique of CNT TFTs which can produce devices of exceptionally high yield, reproducibility as well as low variation in performance. Furthermore, the very fine control of the CNT deposition allows us better device engineering, thus increasing the integrability of CNT transistors into electronic systems. This represents a major step toward low-cost and large-scale production of CNT-based devices.